Renal calyx access does not affect intraoperative blood loss in percutaneous nephrolithotomy: a single-center retrospective study - Luangtangvarodom, Phawat; Tangpaitoon, Teerayut; Liwrotsap, Chatchawet (Insight Urology, 2022)
Objective: Percutaneous nephrolithotomy (PCNL) is one of the most effective ways of dealing with large renal calculi but also comes with a risk of intraoperative blood loss. Previous evidence is contradictory as regards the difference in blood loss between different renal calyx access. We conducted this study to compare intraoperative blood loss between different renal access calyx. Materials and Methods: We conducted a retrospective study analyzing 132 cases of single access PCNL, dividing them into an upper pole group (n = 93) and a non-upper pole group (n = 39). Intraoperative blood loss was calculated from pre-and post-operative hematocrit level, gender, body surface area, and amount of blood transfusion. Blood loss was compared between the two groups using univariable and multivariable analysis. Results: Overall blood loss was 500 ml (IQR 200-814 ml) with a median blood loss of 461 ml (IQR 158-738 ml) in the upper pole group and 650 ml (IQR 332-1233 ml) in non-upper pole group. Median hematocrit change was 2.9% and 3.9% in the upper and non-upper pole groups, respectively. The blood transfusion rate was 4.5% in the upper pole group and 8.3% in the non-upper pole group. The multivariable analysis did not demonstrate any statistically significant difference in average blood loss, hematocrit change or blood transfusion rate. Conclusions: Our study did not find any significant difference in intraoperative blood loss between different renal access routes in PCNL.